SEQUENCE OF A CDNA-ENCODING BOTHROPSTOXIN-I, A MYOTOXIN FROM THE VENOM OF BOTHROPS-JARARACUSSU - Ward, R. J.; Monesi, N.; Arni, R. K.; Larson, R. E.; Pacolarson, M. L. (Elsevier B.V., 1995)
With the aim of further understanding the structure/function relationships in the membrane-damaging activity of the Lys(49) phospholipase A(2) (Lys(49)-PLA(2)) sub-family, we used PCR (polymerase chain reaction) on total venom gland cDNAs from Bothrops jararacussu with degenerate oligodeoxyribonucleotides encoding the N- and C-termini of myotoxin II, a Lys(49)-PLA(2) from Bothrops asper. A 350-bp cDNA coding for bothropstoxin I (BtxtxI) was amplified. Sequencing of the amplified fragment shows that BtxtxI has a Lys(49), and comparison with the known structure of myotoxin II showed that the amino acids involved in the formation of a novel dimeric structure in this protein were also conserved.
Keywords: PHOSPHOLIPASE; LYS(49); CA2+-INDEPENDENT; MEMBRANE DAMAGING; SNAKE TOXIN